Antitumor properties of griseofulvin and its toxicity - Yu, Nanqiong; Fu, Yixiao; Fan, Qingkui; Lin, Li; Ning, Zhifeng; Leng, Dongze; Hu, Meichun; She, Tonghui (Frontiers in Pharmacology, 2024)
Griseofulvin (GF), which is mainly extracted from Penicillium griseofulvum, is a heat-resistant, chlorine-containing non-polyene antifungal antibiotic. Previous research shows that GF has a variety of pharmacological effects, such as anti-inflammatory, antifungal, antiviral, and antitumor effects. In recent years, GF has received extensive attention for its antitumor effects as a natural compound, offering a low price, a wide range of uses, and other beneficial characteristics. However, no comprehensive review of GF pharmacological activity in tumors has been published so far. In order to fully elucidate the antitumor activities of GF, this review focuses on the antitumor potential and toxicity of GF and its derivatives, based on a literature search using PubMed, Web of Science, and other databases, to lay a good foundation for further research of GF and the development of new drugs for antitumor activities.